Pengaruh Video Pembelajaran Berbasis Edpuzzle pada Materi Fusion Pastry Bakery terhadap Level Kognitif dan Kinerja Siswa - Asmahda, Rahadatul; Miranti, Mauren Gita; Purwidiani, Niken; Kuncoro, Andika (Ainara Journal (Jurnal Penelitian dan PKM Bidang Ilmu Pendidikan), 2023)
Edpuzzle is one of the interactive video-based e-learning platforms that is often used in the world of education. Research objectives are Knowing the effect of using Edpuzzle videos on students' cognitive levels, knowing the influence of using Edpuzzle videos on student practicum performance and knowing the influence of Edpuzzle videos on cognitive levels and practicum performance simultaneously. The type of research used is a type of quantitative research with a quasi-experimental design research model (Pseudo-Experiment). The variables used were three variables with one independent variable (X: Edpuzzle Learning Video) and two dependent variables (Y1: Cognitive Level and Y2: Practicum Performance). Data collection is carried out using test methods and performance observation. The data was processed with Simple Regression T Test and Manova Test. After that, discussion and conclusion are drawn from the problem formulation. From this writing, it is concluded that the Sig value in each hypothesis shows a > number of 0.05 probability, it can show that there is a significant influence between cognitive level and practicum performance and there is an influence of both on fusion pastry bakery learning materials using the Edpuzzle video-based learning method. In line with the conclusions above, it is hoped that the use of Edpuzzle learning media can provide something new to the world of education. And educators can apply innovative learning media to students.